Abnormal serum lipid profile in Brazilian police officers with post-traumatic stress disorder - Maia, Deborah Bezerra (2007)
BACKGROUND: To measure the serum lipid composition of a sample of Brazilian police officers with and without PTSD regularly exposed to potentially traumatic situations. METHODS: A cross-sectional survey was conducted with 118 active duty male police officers. Serum concentrations for total cholesterol, LDL-C, HDL-C, and triglycerides were enzymatically determined. Body mass index (BMI) was obtained for each participant. RESULTS: Officers with PTSD exhibited significantly higher serum total cholesterol, LDL-C and triglycerides levels than those without PTSD. Total cholesterol and triglycerides, but not LDL-C, remained associated with PTSD diagnosis after controlling for confounding influences (i.e. socio-demographics, BMI, and tobacco, alcohol and medication use). LIMITATIONS: The sample size was small. A nutritional interview was employed instead of established scales to assess alimentary habits, tobacco or alcohol consumption. A self-report screening tool was used to assess the prevalence of PTSD. CONCLUSIONS: The association between PTSD and abnormal serum lipid profile and a tendency to exhibit higher BMI suggests that individuals with PTSD may be at increased risk for developing metabolic syndrome, a condition that by itself could account for many of the most serious PTSD-related physical health problems.